Motivational Interviewing As an Adjunct to Periodontal Therapy—A Systematic Review - Kopp, Svenja L.; Ramseier, Christoph A.; Ratka-Krüger, Petra; Woelber, Johan P. (Frontiers in Psychology, 2017)
Aim Periodontal therapy is highly dependent on patient´s long-term adherence with regard to oral hygiene, diet and regular check-ups at the dentist. Motivational Interviewing (MI) is a client-centered, directive method for encouraging patients´ behavioral health change. Aim of this systematic review was to reveal the effects of MI as an adjunct to periodontal therapy. Methods Two databases PubMed and Web of Science were searched for randomized controlled clinical trials. Articles were included when using MI as an adjunct to periodontal therapy. Two authors independently coded the relevant articles. Results The search yielded 402 articles. After analysis and exclusion, in total 5 papers could be included. The quality of the articles ranged between 72-88%. The two independent raters showed a high inter-rater reliability (Cohens-Kappa= 0,89). In two studies MI showed a significant positive effect on BOP and PI. One study showed improvement of self-efficacy in interdental cleaning. Two studies showed no influence of MI on periodontal parameters of the patients. Conclusion The use of MI as an adjunct to periodontal therapy might have a positive influence on clinical periodontal parameters (plaque values, gingival and periodontal inflammation) and psychological factors related to oral hygiene (self-efficacy). Due to the low body of evidence further studies are needed. Future studies should include fidelity measures of the applicated MI, a high number of counsellors, several MI sessions, and long-term study follow-up to show potential effects.